Cardiovascular Actions and Clinical Outcomes With Glucagon-Like Peptide-1 Receptor Agonists and Dipeptidyl Peptidase-4 Inhibitors. Issue 9 (29th August 2017) - Nauck, Michael A.; Meier, Juris J.; Cavender, Matthew A.; Abd El Aziz, Mirna; Drucker, Daniel J.
Abstract : Potentiation of glucagon-like peptide-1 (GLP-1) action through selective GLP-1 receptor (GLP-1R) agonism or by prevention of enzymatic degradation by inhibition of dipeptidyl peptidase-4 (DPP-4) promotes glycemic reduction for the treatment of type 2 diabetes mellitus by glucose-dependent control of insulin and glucagon secretion. GLP-1R agonists also decelerate gastric emptying, reduce body weight by reduction of food intake and lower circulating lipoproteins, inflammation, and systolic blood pressure. Preclinical studies demonstrate that both GLP-1R agonists and DPP-4 inhibitors exhibit cardioprotective actions in animal models of myocardial ischemia and ventricular dysfunction through incompletely characterized mechanisms. The results of cardiovascular outcome trials in human subjects with type 2 diabetes mellitus and increased cardiovascular risk have demonstrated a cardiovascular benefit (significant reduction in time to first major adverse cardiovascular event) with the GLP-1R agonists liraglutide (LEADER trial [Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Ourcome Results], −13%) and semaglutide (SUSTAIN-6 trial [Trial to Evaluate Cardiovascular and Other Long-term Outcomes with Semaglutide], −24%). In contrast, cardiovascular outcome trials examining the safety of the shorter-acting GLP-1R agonist lixisenatide (ELIXA trial [Evaluation of Lixisenatide in Acute Coronary Syndrom]) and the DPP-4 inhibitors saxagliptin (SAVOR-TIMI 53 trial [Saxagliptin Assessment of Vascular Outcomes Recorded in Patients With Diabetes Mellitus-Thrombolysis in Myocardial Infarction 53]), alogliptin (EXAMINE trial [Examination of Cardiovascular Outcomes With Alogliptin Versus Standard of Care in Patients With Type 2 Diabetes Mellitus and Acute Coronary Syndrome]), and sitagliptin (TECOS [Trial Evaluating Cardiovascular Outcomes With Sitagliptin]) found that these agents neither increased nor decreased cardiovascular events. Here we review the cardiovascular actions of GLP-1R agonists and DPP-4 inhibitors, with a focus on the translation of mechanisms derived from preclinical studies to complementary findings in clinical studies. We highlight areas of uncertainty requiring more careful scrutiny in ongoing basic science and clinical studies. As newer more potent GLP-1R agonists and coagonists are being developed for the treatment of type 2 diabetes mellitus, obesity, and nonalcoholic steatohepatitis, the delineation of the potential mechanisms that underlie the cardiovascular benefit and safety of these agents have immediate relevance for the prevention and treatment of cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.